2022
DOI: 10.1039/d2cc03058f
|View full text |Cite
|
Sign up to set email alerts
|

Acetate promotes the formation of NiRu/NiO towards efficient hydrogen evolution

Abstract: The introduction of acetate in the precursor of metal–organic frameworks (MOFs) turns the final product from MOFs to NiRu/Ni(OH)2. Followed by annealing treatment, the obtained NiRu/NiO catalyst exhibits high hydrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Figure 3d displays the O 1s spectrum of Ni-MnO 2 , and the significant peaks at 530.0 and 532.4 eV are assigned to lattice oxygen from Ni-MnO 2 , and O−H bond from adsorbed surface water, respectively. 57 In conclusion, all the results above clearly demonstrated that Ni-doped MnO 2 nanosheet arrays on NF were successfully synthesized.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 3d displays the O 1s spectrum of Ni-MnO 2 , and the significant peaks at 530.0 and 532.4 eV are assigned to lattice oxygen from Ni-MnO 2 , and O−H bond from adsorbed surface water, respectively. 57 In conclusion, all the results above clearly demonstrated that Ni-doped MnO 2 nanosheet arrays on NF were successfully synthesized.…”
Section: Resultsmentioning
confidence: 95%
“…The Ni 2p spectrum of Ni-MnO 2 in Figure c shows two main peaks positioned at 855.4 and 872.9 eV, which are ascribed to Ni 2+ 2P 3/2 and Ni 2+ 2P 1/2 , together with two corresponding satellite peaks. Figure d displays the O 1s spectrum of Ni-MnO 2 , and the significant peaks at 530.0 and 532.4 eV are assigned to lattice oxygen from Ni-MnO 2 , and O–H bond from adsorbed surface water, respectively . In conclusion, all the results above clearly demonstrated that Ni-doped MnO 2 nanosheet arrays on NF were successfully synthesized.…”
Section: Resultsmentioning
confidence: 97%
“…Relative to mono-metallic components, bi-metallic catalysts can exhibit unique catalytic properties due to the alloy effect by optimizing the binding strength of intermediates. 37,38 In this regard, various bi-metallic systems with bicontiunous nanoporous structures were constructed via the dealloying method for the HER. For example, Lu et al developed a novel non-precious bimetallic Cu–Ti catalyst with a bimodal pore size distribution by selectively dealloying an Al–Cu–Ti alloy precursor (Fig.…”
Section: Nanoporous Her Electrocatalystsmentioning
confidence: 99%
“…and Ni 2p 3/2 peaks analogous to the binding energy in the range of 850 to 869 eV and 870 to 885 eV, respectively [21]. Figure 5c represents the core-level spectra of the Ni 2p, were all the peaks were indexed as per the standard literature [21].…”
Section: X-ray Photoelectron Spectroscopic Analysismentioning
confidence: 99%
“…and Ni 2p 3/2 peaks analogous to the binding energy in the range of 850 to 869 eV and 870 to 885 eV, respectively [21]. Figure 5c represents the core-level spectra of the Ni 2p, were all the peaks were indexed as per the standard literature [21]. The satellite peak Ni 2p when the other component at 533.25 eV was may be attributed to an oxygen atom in C -OH bond (O = C -OH) [22].…”
Section: X-ray Photoelectron Spectroscopic Analysismentioning
confidence: 99%